Recombinant Swinepox Virus Expressing Glycoprotein E2 of Classical Swine Fever Virus Confers Complete Protection in Pigs upon Viral Challenge - Lin, Huixing; Ma, Zhe; Chen, Lei; Fan, Hongjie (Frontiers in Veterinary Science, 2017)
Classical swine fever (CSF) is a highly contagious and serious viral disease that affects the pig industry worldwide. The glycoprotein E2 of the classical swine fever virus (CSFV) can induce neutralizing antibodies, and it is widely used for novel vaccine development. To explore the development of a vaccine against CSFV infections, the gene of glycoprotein E2 was inserted into the swinepox virus (SPV) genome by homologous recombination. The culture titers of rSPV-E2 remained at about 4.3 ×106 TCID50 for more than 60 passages in PK15 and ST cell lines. The rSPV-E2 could not be replicated in Vero, MDBK or other non-porcine cell lines. After 2-3 passages, the SPV specific gene of rSPV-E2 could not been detected in the non-porcine cell culture. To evaluate the immunogenicity of rSPV-E2, twenty CSFV seronegative minipigs were immunized with rSPV-E2, a commercial C-strain vaccine, wild-type SPV (wtSPV; negative control), or PBS (a no-challenge control). After challenge with CSFV, pigs in the rSPV-E2-immunized group showed significantly shorter fever duration compared with the wtSPV-treated group (P < 0.05). E2-specific antibodies in the rSPV-E2-immunized group increased dramatically after vaccination and increased continuously over time. CSFV genomic copies in the serum of rSPV-E2-immunized pigs were significantly less compared with the wtSPV-treated group at all time points after challenge (P < 0.01). Significant reduction in gross lung lesion scores, histopathological liver, spleen, lung, and kidney lesion scores were noted in the rSPV-E2-immunized group compared with the wtSPV-treated group (P < 0.01). The results suggested that the recombinant rSPV-E2 provided pigs with significant protection from CSFV infections; thus, rSPV-E2 offers proof of principle for the development of a vaccine for the prevention of CSFV infections in pigs.